2019
DOI: 10.4049/jimmunol.1800081
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Induces Glomerular Endothelial Cell–Specific Expression of Complement Factor H via the −1635 AP-1 Binding Site

Abstract: Cadmium (Cd) is an environmental toxin that induces nephrotoxicity. Complement factor H (CFH), an inhibitor of complement activation, is involved in the pathogenesis of various renal diseases. In this study, we investigated the effects of Cd on CFH production by the kidney. In C57B6/J mice, an increased CFH level was found in renal blood and glomerular endothelial cells after Cd treatment. In vitro, Cd induces an increased CFH secretion and mRNA expression in human renal glomerular endothelial cells but not in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 55 publications
(61 reference statements)
2
12
0
Order By: Relevance
“…FH is present in the glomerulus and microvasculature (arrow). This is in line with our earlier results 40 and that of several others such as Zoshima et al 41 and Chen et al, 35 revealing the expression of FH in the glomerulus.…”
Section: Immunofluorescence Reveals Fh Expression In Kidneyssupporting
confidence: 94%
See 1 more Smart Citation
“…FH is present in the glomerulus and microvasculature (arrow). This is in line with our earlier results 40 and that of several others such as Zoshima et al 41 and Chen et al, 35 revealing the expression of FH in the glomerulus.…”
Section: Immunofluorescence Reveals Fh Expression In Kidneyssupporting
confidence: 94%
“…34 Further, studies reveal that cadmium increases the expression of FH in glomerular EnCs through c-Jun N-terminal kinase signaling. 35 In addition, FH in the glomeruli partially colocalized with CD31 in hepatic FH-deficient mice, showing endothelial presence. 36 Our studies for the first time show that the absence of intrinsic FH alters gene expression in cultured kidney EnCs (KEnCs).…”
Section: Translational Statementmentioning
confidence: 93%
“…The immunofluorescence was performed by staining with a rabbit polyclonal antibody against human/mouse VE-Cadherin (1:200; ab33168, Abcam) and a Goat Anti-Rabbit IgG H&L (Alexa Fluor 488) (1:200; ab150077, Abcam) as previously described. 27 Then cells were mounted with ProLong® Gold antifade Reagent with DAPI (Life Technologies). Images were captured using Leica SP5 Laser scanning confocal microscope.…”
Section: Immunofluorescencementioning
confidence: 99%
“…Exploring the mRNA expression for Cfh in the kidney showed that the expression was identical in the WT and hepatoFH −/− mice and was not affected by PHZ injection (Figure 5B). Exploring of FH staining in mouse kidney has been tricky and previous studies failed to detect it despite the clear evidence for mRNA production by various renal cell populations (26)(27)(28)(29)(30)(31). The reason for this lack of staining in previous studies vs. the positive staining detected here is unclear and is likely related to the experimental conditions.…”
Section: Fh Is Present In the Mouse Kidneymentioning
confidence: 56%